Discrete non-integer order model of synchronous generator for power hardware-in-the-loop implementation - Racewicz, Szymon; Kutt, Filip; Sienkiewicz, Łukasz; Michna, Michał; Ryndzionek, Roland (Bulletin of the Polish Academy of Sciences Technical Sciences, 2025)
Non-integer order modelling is used for a better description of different natural physical phenomena, which leads to more compact and knowledge-based models. The main objective of the presented study is to apply the non-integer order model of a synchronous generator (SG) in the power hardware-in-the-loop (PHIL) technique, which is readily used for design, research and development, maintenance, or service purposes. The developed model was prepared and run in the MATLAB/Simulink software using a discrete solver. To discretize the non-integer order model, the Z-transform was applied and the half-order derivatives and integrals present in the model equations were evaluated using Oustaloup approximation. Finally, the model was validated on the measurements of the 125 kVA SG connected to the active-reactive loads of different values and compared with the classical integer order one.